Optimizing antibiotic stewardship and reducing antimicrobial resistance in Central Asia: A study protocol for evidence-based practice and policy - Lisa Lim; Laura Kassym; Assiya Kussainova; Bibigul Aubakirova; Yuliya Semenova (PLoS ONE, 2025)
Antimicrobial resistance (AMR) poses a significant global health challenge, prompting the World Health Organization (WHO) to stress the importance of monitoring antibiotic consumption and sales to address AMR effectively. This study protocol aims to optimize antibiotic stewardship and combat AMR in Central Asia through evidence-based practices and policies. The protocol includes objectives such as conducting systematic reviews of interventions to promote judicious antibiotic use, assessing antibiotic consumption trends, and investigating antibiotic overuse practices among healthcare providers. The study aims to raise awareness among stakeholders to enhance appropriate antibiotic prescribing practices. By establishing regulatory frameworks, monitoring policies’ effectiveness, and providing training programs for healthcare professionals, this study seeks to contribute to the global efforts in combating AMR and promoting prudent antibiotic use.